Multiple equilibrium configurations in river-dominated deltas - L. Durante; N. Tambroni; M. Bolla Pittaluga (Earth Surface Dynamics)
The morphological evolution of river deltas is a complex process influenced by both natural factors and human interventions. The stability and predictability of flow distribution within delta channels are critical for human settlements; however, this requirement conflicts with the natural tendency of deltas to avulse towards the most hydraulically efficient branch. This study examines the existence of alternative equilibrium states within deltaic systems, highlighting key internal feedback mechanisms among delta branches through a novel theoretical model tailored to river-dominated delta channels. In particular, the analysis identifies the total length of delta branches extending toward the downstream end as the primary factor governing the stability of individual bifurcations within the delta. Additionally, the spacing between internal bifurcation nodes plays a secondary role by influencing flow partitioning through feedback mechanisms that modify the free-surface elevation at the bifurcation node. For deltas exhibiting significant asymmetries in either length or width, a threshold condition emerges, reducing the number of possible equilibrium states. Focusing on the Po River Delta, Italy, as a case study, we examine equilibrium variability and identify potential avulsion sites. Our findings provide a valuable framework for predicting future shifts in deltaic morphology and informing management strategies that reconcile natural delta evolution with infrastructural and economic requirements.